«Proceedings of Agricultural Botany» – professional edition of the Agricultural Scientific Committee of Ukraine - Hryshchenko, T. R. (History of science and technology, 2016)
A content analysis of the professional edition of «Proceedings of Agricultural Botany», which in 1926–1927 published a leading methodically and coordination center of agricultural science – Agricultural Scientific Committee of Ukraine (1918-1927) is observed in the article. The prerequisites of the journal, unsuccessful attempts to print the first volume, its rebirth and recognition in the scientific community are revealed.